Prevalence of amoebiasis and associated risk factors among population in Duhok city, Kurdistan Region, Iraq - Hasan, Haliz Khalid; Mero, Wijdan Mohammed Salih; Mohammed, Ahmed Basheer (The Journal of Infection in Developing Countries, 2023)
Introduction: Entamoeba histolytica, a protozoan parasite, is the third major contributor to human mortality and morbidity outside of malaria and schistosomiasis. The purpose of this cross-sectional study was to estimate the prevalence of Entamoeba spp. among outpatients of two teaching hospitals in Duhok city who agreed to participate in the study from April 2021 to March 2022 to assess the impact of associated risk variables on the infection rate. Methodology: Stool specimens were collected from outpatients suffering from diarrhea and other gastrointestinal symptoms in two teaching hospitals: Azadi and Heevi Pediatric in Duhok city, Kurdistan Region- Iraq. The collected stool specimens were examined macroscopically, followed by microscopic examination using the direct wet mount and zinc sulfate flotation methods, respectively. Result: Infection with Entamoeba species was recorded in 21.68% (562/2592) of the analyzed specimens. Males had a significantly higher infection rate than females (67.43% vs. 32.56%). This difference was statistically significant (p < 0.000). The highest rate was seen in the age group 1–10 years (p < 0.001). Lower levels of education, low incomes, eating unwashed fruits and vegetables, drinking well water, eating frequently outside of homes, not using antidiarrheal medications and living in overcrowded families were risk factors that showed high levels of infection (p < 0.0001). Conclusions: The present study concluded that improving living conditions, providing clean water, and promoting health education programs are essential to reduce the rate of this disease among the population.